(untitled) (Texas Journal of Medical Science, 2025)
The type of infant feeding plays a crucial role in metabolic adaptation and long-term health outcomes. This study aimed to evaluate metabolic status indicators in children depending on the type of feeding during infancy. A total of 124 children were followed longitudinally for 14 years. Clinical and laboratory assessments included complete blood count, biochemical tests, and lipid profile analyses (LDL, HDL, triglycerides, and total cholesterol). Children who were exclusively breastfed demonstrated optimal lipid and carbohydrate metabolism parameters. In contrast, those who received mixed or artificial feeding showed signs of dyslipidemia, characterized by significantly higher triglyceride (1.2 ± 0.08 mmol/L vs. 0.74 ± 0.08 mmol/L, p < 0.05) and LDL levels (3.4 ± 0.11 mmol/L vs. 2.0 ± 0.01 mmol/L, p < 0.05). Early rapid weight gain was more frequent among artificially fed infants and was associated with later metabolic imbalance. These findings suggest that exclusive breastfeeding contributes to stable lipid and carbohydrate metabolism and helps prevent early metabolic disturbances. The type of feeding and early child care practices are key determinants of metabolic adaptation and prevention of obesity-related disorders in adolescence.